The schemata of the stars : - Paschos, E. A. (World Scientific, 1998)
An edited version and translation of a Byzantine article which contains advanced astronomical ideas and pre-Copernican diagrams. The article presents improvements on ancient and late-medieval astronomy. The authors of the book survey the development of astronomical models from Ptolemy to Byzantium and compares them mathematically with the works of Arab astronomers, as well as with the heliocentric system of Copernicus and Newton.